Linguistic Politeness Issues in Child-Parent Communication: A Pragmatic Study Based on Leech’s Framework: Kajian Pragmatik Geoffrey leech - Melisa, Luluk; Purnomo, Danang Try; Paramita, Santi (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study investigates linguistic politeness issues in communication between children aged 6–12 years and their parents in Ngarap-ngarap Village, Wonogiri, employing Geoffrey Leech’s pragmatic framework. Using a qualitative approach, data were gathered through semi-structured interviews and observations of 12 families to identify forms of politeness, causes of violations, and their impacts on family relationships. Findings indicate that children predominantly use boso kromo inggil, reflecting Javanese cultural norms, but violations occur due to peer influence, adolescent emotions, and digital media exposure, particularly breaching the maxims of approbation and agreement. Politeness fosters emotional closeness and family harmony, whereas violations cause temporary emotional tension. Linguistic factors (diction, speech acts), social factors (peer influence, Javanese culture), and technology shape these issues. The study underscores the need for linguistic politeness education integrating unggah-ungguh and digital literacy to strengthen family bonds and preserve cultural values.